Colchicine-induced variations in survival rate and morphological characteristics of water yam (Dioscorea alata) - Ajayi, A.T.; Adesoye, A.I.; Asiedu, Robert; Sartie, A.M. (2010)
The effects of 0.2% aqueous solution of colchicine on the survival rate and morphological features of five accessions of Dioscorea alata were investigated. Sprouting buds of two month old plants were treated with 0.2% colchicine and their performances were monitored until maturity. Survival of buds was lower in all the treated plants (ranging between 6.25% and 8.75%) compared to controls (between 13.25% and 15.25%). However, colchicine treated vines had higher survival rates when exposed to drought (13.8% - 24%) compared to controls (7.2% - 16.69%). Higher number of leaves, larger leaf width and fewer numbers of stomata were observed among the treated plants. The survival of buds between the treated plants and control plants was signifi cantly different at P ≤ 0.05. The treated and non-treated plants were also signifi cantly different at P ≤ 0.05 for leaf width in accessions TDa02/00246, TDa98/00116 and TDa99/00240, and for stomata number in accessions TDa02/00151 and TDa02/00246. Our results suggest that colchicine can be used to induce mutagenic changes in yam which may be of agronomic importance in the production of the crop.